Factors Affecting Housing Buying Decision in Nakhon pathom District - Naewkhamdee, Narathip; Piakson, Praputhson; Thapchula, Krit; Leangruksa, Thunyaporn (Journal of Management Science Nakhon Pathom Rajabhat University, 2020)
This research study with the objectives 1) to study the level of marketing mix factors And the level of decision making that affects the decision to buy housing in Nakhon Pathom Province 2). To compare personal characteristics factors and marketing mix factors affecting the decision to purchase housing in Nakhon Pathom Province. The samples used in this research were those who bought housing in Nakhon Pathom province. Using Convenience Sampling, 400 people using questionnaires as a tool to collect data The statistics used in the analysis were frequency, percentage, mean and standard deviation. Hypothesis testing with statistics, t-test, one-way ANOVA and multiple regression analysis The study indicated that 1. The results of the study of factors affecting the decision to purchase housing in Nakhon Pathom Province showed that the overall score was at a high level. The first three evaluations are the product price side. And process respectively. The results of the study of purchasing decision levels. The search for information is first priority, followed by problem awareness. The decision to buy after buying behavior and the final assessment of alternatives 2. The comparison results showed that personal characteristics factors such as age, occupation, status, average income per month and the decision to purchase housing in Nakhon Pathom province is different with statistical significance 0.05 and the results of marketing mix factors Consists of creating Physical presentation Product Marketing promotion In terms of distribution channels and price, the decision to buy housing in Nakhon Pathom province is different with statistical significance at the level of 0.05. Article history : Received 6 June 2019 Revised 17 July 2019 Accepted 22 July 2019 SIMILARITY INDEX = 1.25 %